Examining the factors of the Technology Acceptance Model for Counselor Education graduate students in CACREP-accredited programs - Chow, Rebeca Isabel (Kansas State University, 2019)
As higher education continues to integrate technology, the counselor education field has evolved and recognized the importance of graduate students’ attitudes towards technology acceptance of a wide array of technology in their training programs (Burt, Gonzalez, Swank, Ascher, & Cunningham, 2011; Kennedy, 2011; Orr, 2011; Sabella, Poynton, & Isaacs, 2010; Tyler & Sabella, 2004). This study examined the attitudes of counselor education graduate students in CACREP-accredited program towards technology acceptance using the Technology Acceptance Model (TAM) as the theoretical framework for the study. In particular, the purpose of this study was to better understand counselor education graduate students’ attitudes towards technology acceptance as it relates to perceived ease of use, perceived usefulness, technology self-efficacy, and technology anxiety. Participants in the study were 107 graduate students who were enrolled in Fall 2018 at 10 Midwest CACREP-accredited counselor education programs. Data were gathered by an online survey consisting of a demographic questionnaire and four instruments (Technology Acceptance Model Scales, Media and Technology Usage and Attitudes Scale, Technology Self-efficacy Scale, and Technology Anxiety Scale). The results of the hierarchical regression analysis for each of the research questions revealed several significant findings regarding graduate students’ attitudes towards use of technology. For the first research question, perceived ease of use was predicted by technology self-efficacy and technology anxiety. The results indicated perceived ease of use was influenced positively by technology self-efficacy and negatively by technology anxiety. For the second research question, perceived usefulness was predicted by technology self-efficacy and technology anxiety. The results indicated perceived usefulness was influenced positively by technology self-efficacy and negatively by technology anxiety. For the third research question, counselor education graduate students’ attitudes towards the use of technology was predicted by perceived usefulness. In addition, this study found a strong positive relationship between perceived ease of use and perceived usefulness likely due to multicollinearity. Technology plays an increasing role in counselor education programs. Findings from this study provide important information for counselor education programs to consider regarding graduate students’ attitudes towards the use of technology.
Keywords: Counselor education; Technology acceptance; Technology anxiety; Technology self-efficacy; Technology acceptance model